Development Rime Syar'i Business & Administration Management System with Rapid Application Development Method - Melati; Eko Junirianto; Ida Maratul Khamidah (Politeknik Pertanian Negeri Samarinda, 2022)
This research aims to produce an administrative information system design to increase accuracy in data processing and the ability to provide faster information for a business and increase the accuracy of service to consumers. This study also aims to identify information system problems on the system running on Rime Syar'i business and produce a Web-based administrative information application program that includes administrative transactions to produce transaction reports and reports that are needed to facilitate business management. Rime Syar'i. The conclusion obtained from this research is that using a web-based information system, can minimize errors in data processing, increase the effectiveness and efficiency of Rime Syar'i's business work in a better direction, and ease in making reports.